Atomistic observation of the collision and migration of Li on MoSe2 and WS2 surfaces through ab initio molecular dynamics. Issue 40 (3rd October 2017) - Ho, Thi H.; Bui, Viet Q.; Bach Phan, Thang; Kawazoe, Yoshiyuki; Le, Hung M.
Abstract : We present in this study a theoretical investigation of the collision of Li with the MX2 surface (MoSe2 or WS2 ) by employing the Born–Oppenheimer molecular dynamics (MD) approach. Abstract : We present in this study a theoretical investigation of the collision of Li with the MX2 surface (MoSe2 or WS2 ) by employing the Born–Oppenheimer molecular dynamics (MD) approach. In each trajectory, atomic Li is fired toward the two-dimensional monolayer with an inletting kinetic energy of 0.2 eV or 2.0 eV and a chosen striking angle. In total, 84 MD trajectories are analyzed. We observe that Li has a high tendency to migrate on WS2 in most investigated cases (20/21 cases at 0.2 eV inletting kinetic energy and 21/21 cases at 2.0 eV inletting kinetic energy), while the migration probability on MoSe2 is much lower (only 5/21 cases with the inletting kinetic energy of 0.2 eV and 15/21 cases with the inletting kinetic energy of 2.0 eV). Interestingly, our finding shows that the migration probability does not depend on the binding energies of Li–MoSe2 (1.61 eV) and Li–WS2 (1.77 eV), but it is in good agreement with the nudged-elastic-band prediction of migration barriers. In fact, it is the intensity of elastic vibration of the transition metal dichalcogenide layer that plays a very significant role in the migration of Li. During the collision process, Li is able to absorb energy from the layer vibration to jump out from one X–X–X trap to another. Consequently, with the assistance from intensive vibration of WS2, Li would possess higher migration probability on the layer surface. Finally, electronic structure analysis on various interacting Li–MX2 configurations is performed. From Bader charge estimation, we observe that WS2 tends to establish more charge transferability with Li. Moreover, when Li approaches closer to the S/Se layer, the hybridization of Li-2s and Mo-4d (or W-5d) orbitals results in a magnetic moment (up to ∼1 μ B ).